GE_GERICHTE P/5107/2013 vom 4. Mai 2016 - GE Cour de justice (2016)
ACTE D'ACCUSATION; IN DUBIO PRO REO; VIOLENCE CONTRE LES AUTORITÉS; DÉFENSE D'OFFICE ; ASSISTANCE JUDICIAIRE | CPP 325 ; CEDH 6.2 ; CP 285 ; CPP 135.1